Microring resonator made by ion-exchange technique for detecting the CO2, H2O, and NaCl as cladding layer - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Kouhdaragh, Vahid; Seyedi, Seyedalireza A.; Yupapin, Preecha Promphan (Elsevier, 2019)
A system of Microring Resonator (MRR) based the comb-like sensor devices has been simulated. We present a Silicon-On-Insulator (SOI) ring resonator based on refractive index sensor. The novelty of the architecture lies in the capability to sense the shifts of multiple peaks simultaneously with an MRR waveguide. The behavior of optical MRRs, especially when functioning as refractive index sensors, is studied. Resonant wavelength, i.e. the wavelength at which the transmission spectrum exhibits a dip (peak) depends on the geometrical characteristics of the circular waveguide and the effective refractive index of the propagating mode. The previous studies have shown that the depth and vertical symmetry of buried waveguides are noticeably affected by the field perturbation. One of cost effective and low loss methods can be the technology known as ion-exchange which uses the glass substrates and the AgNO3/NaNO3 salt-melt at different temperatures and duration can be deposited on the glass substrates. Afterward, an MRR was designed on the glass substrates, where the effect of the carbon dioxide (CO2), Dihydrogen oxide (H2O), and sodium chloride (NaCl) as the cladding on the ion-exchange waveguide studied. Within the compare of the resonance in drop port and throughput port, it can understand that they roughly have the same distance of wavelength in the resonance. H2O is one of the materials showing higher Qfactor and FSR while it was in drop port also in throughput CO2 was the highest in these parameters.